Circuit analysis theory and practice - Robbins, Allan (Delmar, 1994)
This ABET-level (optional calculus introduced, emphasis on problem-solving) introductory DC/AC text covers electrical circuit theory, beginning with foundational theorems and basic DC concepts and advancing through to AC topics.